1992
DOI: 10.1128/aem.58.9.2971-2977.1992
|View full text |Cite
|
Sign up to set email alerts
|

DNA amplification polymorphisms of the cultivated mushroom Agaricus bisporus

Abstract: Single 10-bp primers were used to generate random amplified polymorphic DNA (RAPD) markers from commercial and wild strains of the cultivated mushroom Agaricus bisporus via the polymerase chain reaction. Of 20 primers tested, 19 amplified A. bisporus DNA, each producing 5 to 15 scorable markers ranging from 0.5 to 3.0 kbp. RAPD markers identified seven distinct genotypes among eight heterokaryotic strains; two of the commercial strains were shown to be related to each other through single-spore descent. Homoka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 18 publications
(23 reference statements)
1
14
0
1
Order By: Relevance
“…RAPD-PCR is one of the most sensitive and efficient methods currently available for distinguishing between different strains of a species (10). For instance, RAPD markers distinguished between individual strains and meiotic progeny of the cultivated mushroom Agaricus bisporus (22) and between clinical isolates of the fungal pathogens Histoplasma capsulatum (21) and Cryptococcus neoformans (31). RAPD markers identified strains of the bacterium Xanthomonas campestris pv.…”
mentioning
confidence: 99%
“…RAPD-PCR is one of the most sensitive and efficient methods currently available for distinguishing between different strains of a species (10). For instance, RAPD markers distinguished between individual strains and meiotic progeny of the cultivated mushroom Agaricus bisporus (22) and between clinical isolates of the fungal pathogens Histoplasma capsulatum (21) and Cryptococcus neoformans (31). RAPD markers identified strains of the bacterium Xanthomonas campestris pv.…”
mentioning
confidence: 99%
“…For each primer, ATCC 28759 and ATCC 28760 had indistinguishable RAPD profiles, suggesting that these strains are either duplicates or at least very closely related. Identical RFLP and RAPD fingerprints have been found previously among different strains of another cultivated mushroom, Aguricus bisporus [2,5], and have been used to infer relationship by single-spore descent [2].…”
Section: Resultsmentioning
confidence: 74%
“…Single, arbitrary lo-base oligonucleotides can generate multiple fragments of the L. edodes genome via the polymerase chain reaction and variations in primer-binding sites result in amplification polymorphisms that readily differentiate strains. The same approach has been previously used for strain typing of Agaricus bisporus [2]. A method similar to RAPD, arbitrarily primed PCR, has been shown by Kwan et al [4] to produce unique strain profiles in L. edodes.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, low genetic diversity was revealed by RAPD markers while ISSR and SSR markers showed higher genetic diversity. In mushrooms, RAPDs have been used for diversity assessment, screening of homokaryotic lines and confirmation of hybridization (Khush et al 1992;Sunagawa et al 1995). Chillali et al (1998) used analysis of ITS and IGS regions for evaluation of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%